1993
DOI: 10.1577/1548-8675(1993)013<0186:mbsthm>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Management Briefs: Short-Term Hooking Mortalities of Red Drums and Spotted Seatrout Caught on Single-Barb and Treble Hooks

Abstract: A bstract. hooking mortalities of red drums Sciaenops ocellatus and spotted seatrout Cynoscion nebulosus caught with single-barb hooks were compared with hooking mortalities for those caught with treble hooks in Texas bays in the summers of 1989 and 1990. Natural baits (primarily penaeid shrimp) and artificial baits (spoons, worms, and fish-shaped lures) were used with both hook types. Overall mortality of 121 red drums was 4.1 % at the end of 3 d after capture, and there were no significant (P = 0.67) red dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 14 publications
4
22
0
Order By: Relevance
“…A review of catch-and-release mortality studies concluded that most mortality occurs within 24 h, but a more complete estimate of the mortality should include delayed mortality (i.e., that occurring beyond the first 24 h postrelease; Muoneke and Childress 1994). Typically, a 3-d observation period is used (e.g., see Matlock et al 1993;Malchoff and Heins 1997), and only a few catch-and-release mortality studies use a longer postrelease observation period (e.g., blue cod Parapercis colias were observed for 14 d : Carbines 1999; largemouth bass Micropterus salmoides for 14-21 d: Schramm et al 1987; spotted seatrout Cynoscion nebulosus for 30 d: Stunz and McKee 2006; white seabass Atractoscion nobilis for 90 d: Aalbers et al 2004; and white crappies Pomoxis annularis for 18 months: Colvin 1991). Observations beyond 3 d are difficult because fish must be confined artificially either in the laboratory or in the field, and such confinement may contribute to further stress and mortality.…”
Section: Recent Data From the Marine Recreational Fisherymentioning
confidence: 99%
“…A review of catch-and-release mortality studies concluded that most mortality occurs within 24 h, but a more complete estimate of the mortality should include delayed mortality (i.e., that occurring beyond the first 24 h postrelease; Muoneke and Childress 1994). Typically, a 3-d observation period is used (e.g., see Matlock et al 1993;Malchoff and Heins 1997), and only a few catch-and-release mortality studies use a longer postrelease observation period (e.g., blue cod Parapercis colias were observed for 14 d : Carbines 1999; largemouth bass Micropterus salmoides for 14-21 d: Schramm et al 1987; spotted seatrout Cynoscion nebulosus for 30 d: Stunz and McKee 2006; white seabass Atractoscion nobilis for 90 d: Aalbers et al 2004; and white crappies Pomoxis annularis for 18 months: Colvin 1991). Observations beyond 3 d are difficult because fish must be confined artificially either in the laboratory or in the field, and such confinement may contribute to further stress and mortality.…”
Section: Recent Data From the Marine Recreational Fisherymentioning
confidence: 99%
“…Previous studies have reported little effect of bait and hook types on mortality in this species. Matlock et al (1993) reported no differences among bait and hook types for spotted seatrout in the Texas recreational fishery. In Alabama, Duffy (2002) reported no differences in mortality associated with treble hooks versus single hooks.…”
Section: Stunz and Mckeementioning
confidence: 99%
“…We found no significant relationship between fish length and percent mortality. Previous studies examining spotted seatrout catch-and-release mortality have not considered the relationship between fish length and mortality (Matlock and Dailey 1981;Hegen et al 1987;Matlock et al 1993;Murphy et al 1995;Duffy 2002), and this relationship can have important implications under different management scenarios (Muoneke and Childress 1994). The limited nature of investigations on size-related mortality is probably related to the difficulty of catching sufficient numbers of large trout to carry out replicated studies.…”
Section: Stunz and Mckeementioning
confidence: 99%
See 2 more Smart Citations